Advanced thermal simulation of SiGe:C HBTs including back-end-of-line. (December 2016) - d'Alessandro, Vincenzo; Magnani, Alessandro; Codecasa, Lorenzo; Rinaldi, Niccolò; Aufinger, Klaus
Abstract: Advanced 3-D thermal simulations of state-of-the-art SiGe:C HBTs are performed, which ensure improved accuracy with respect to conventional approaches. The whole back-end-of-line architecture is modeled so as to account for the cooling effect due to the upward heat flow. Moreover, a nonuniform power density is considered to describe the heat source, and thermal conductivity degradation effects due to germanium, doping profile, and phonon scattering in narrow layers are implemented. The numerical thermal resistances are compared with those experimentally evaluated by means of a robust technique relying on the temperature dependence of the base-emitter voltage. Highlights: Accurate 3-D thermal simulations of SiGe:C HBTs including the BEOL are performed. A realistic nonuniform power density obtained by device simulation is considered. Thermal conductivity degradation due to Ge, doping, scattering with edges is included. FEM thermal resistances are compared with those measured by an improved dc technique. The individual contribution of all effects on the heat propagation is quantified.